Composite nanofiller, preparation method thereof and coating
Through ball milling and silane coupling agent modification treatment, highly dispersible composite nanofillers were prepared, which solved the agglomeration problem of nanofillers in the coating and improved the performance and stability of the coating.
Patent Information
- Application Number
- CN202411192323.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-20
AI Technical Summary
Due to its high specific surface area and surface energy, composite nanofillers are prone to agglomeration in the coating, resulting in uneven distribution and performance degradation, affecting the final performance of the coating.
By mixing graphene and graphene oxide and ball milling, adding silica and titanium dioxide for multiple ball milling, combining surface modification treatment of silane coupling agent, composite nanofillers with high dispersion and stability were prepared.
It significantly improves the dispersion of graphene and graphene oxide, enhances the corrosion resistance, toughness and impact resistance of the paint, ensures the long-term stable dispersion of fillers in the paint system, and is suitable for a variety of application scenarios.
Smart Images

Figure CN119161749A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of nanomaterials, and in particular to a composite nanofiller and a preparation method and coating thereof. Background Art
[0002] With the development of nanotechnology, the introduction of composite nanofillers has opened up a new way to improve material performance. However, due to their extremely high specific surface area and surface energy, composite nanofillers are very likely to agglomerate in liquid matrices such as coatings to form larger particle aggregates. This agglomeration phenomenon not only seriously weakens the inherent nano effect of nanofillers, but also leads to their uneven distribution in the coating system, which in turn affects the final performance of the coating.
[0003] The above contents are only used to assist in understanding the technical solution of the present application and do not constitute an admission that the above contents are prior art. Summary of the invention
[0004] The main purpose of the present application is to provide a composite nanofiller and a preparation method and coating thereof, aiming to improve the dispersion uniformity of the composite nanofiller.
[0005] To achieve the above object, the present invention provides a method for preparing a composite nanofiller, comprising the following steps:
[0006] Mixing graphene and graphene oxide and ball-milling them once to obtain a first powder;
[0007] Adding silicon dioxide to the first powder and performing secondary ball milling to obtain a second powder;
[0008] Adding titanium dioxide to the second powder and ball-milling the mixture three times to obtain a third powder;
[0009] The talcum powder, the silane coupling agent and the third powder are mixed and dispersed to prepare a composite nano filler.
[0010] In one embodiment, the particle size of the silicon dioxide is 200 to 500 nm;
[0011] And / or, the particle size of the titanium dioxide is 200 to 500 nm.
[0012] In one embodiment, the composite nanofiller includes, by weight: 5 to 30 parts of a mixture of graphene and graphene oxide, 40 to 110 parts of silicon dioxide, 30 to 80 parts of titanium dioxide, 100 to 130 parts of talc and 4 to 7 parts of a silane coupling agent.
[0013] In one embodiment, the mass ratio between graphene and graphene oxide is 1:(0.05-0.3).
[0014] In one embodiment, the grinding time of the first ball milling is 1.5 to 2 hours, the grinding temperature is 25 to 50° C., the main disk speed is 200 to 400 rpm, and the grinding jar speed is 300 to 450 rpm;
[0015] And / or, the grinding time of the secondary ball milling is 2 to 3 hours, the main disc speed is 180 to 250 rpm, and the grinding jar speed is 200 to 320 rpm;
[0016] And / or, the grinding time of the three ball millings is 2 to 3 hours, and the grinding temperature is less than 65°C.
[0017] In one embodiment, the silane coupling agent includes: a first silane coupling agent and a second silane coupling agent, and the step of mixing and dispersing talcum powder, the silane coupling agent and the third powder to prepare the composite nanofiller includes:
[0018] providing a first silane coupling agent solution;
[0019] Mixing the third powder with the first silane coupling agent solution;
[0020] Talc powder and a second silane coupling agent are added and ultrasonically dispersed to prepare a composite nanofiller.
[0021] In one embodiment, the first silane coupling agent includes: at least one of KH-550, KH-560 and KH-570;
[0022] And / or, the second silane coupling agent includes at least one of KH-550, KH-560, KH-570 and KH-792.
[0023] The embodiment of the present application also provides a composite nanofiller, which is prepared by the above method.
[0024] The embodiment of the present application further provides a coating, which includes a composite nanofiller prepared by the composite nanofiller preparation method as described above.
[0025] In one embodiment, the coating further comprises: epoxy resin, wherein the mass ratio between the composite nanofiller and the epoxy resin is (3-5):(40-85).
[0026] One or more technical solutions proposed in this application have at least the following technical effects: Provide a method for preparing a composite nanofiller, by mixing graphene and graphene oxide and ball milling once to obtain a first powder, then adding silicon dioxide to the first powder and ball milling twice to obtain a second powder; then adding titanium dioxide to the second powder and ball milling three times to obtain a third powder; then mixing and dispersing talcum powder, a silane coupling agent and the third powder to obtain a composite nanofiller in the form of a slurry. This application uses silicon dioxide and titanium dioxide with high hardness as auxiliary grinding media, so that graphene can be attached to silicon dioxide and / or titanium dioxide, significantly increasing the contact area between graphene and hard particles during ball milling, thereby effectively improving the dispersibility of graphene and graphene oxide. Furthermore, through the surface modification treatment of the silane coupling agent, the compatibility between the filler and the coating matrix in subsequent applications is promoted, ensuring the long-term stable dispersion of the filler in the coating system. In addition, the graphene oxide dispersed in the composite nanofiller can not only increase the corrosion resistance, toughness and impact resistance of the coating during the application process, but also play a certain dispersion and barrier role, which is more conducive to the uniformity and stability of the composite nanofiller during application, making the prepared composite nanofiller suitable for a variety of application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a flow chart of a method for preparing a composite nanofiller according to an embodiment of the present application.
[0028] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0030] Hereinafter, the embodiment of the method for recovering lithium from waste lithium iron phosphate batteries of the present application is specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the accompanying drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0031] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0032] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0033] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0034] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0035] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0036] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0037] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and understandable, the technical solution of the present application is further described below in conjunction with the accompanying drawings and embodiments. However, the present application is not limited to the listed embodiments, and should also include any other known changes within the scope of the rights claimed in the present application.
[0038] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present application. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0039] In order to better understand the technical solution of the present application, a detailed description will be given below in conjunction with the accompanying drawings and specific implementation methods.
[0040] In conventional technology, composite nanofillers are very likely to agglomerate in liquid matrices such as coatings due to their extremely high specific surface area and surface energy, forming large-sized particle aggregates. This agglomeration phenomenon not only seriously weakens the inherent nano effect of nanofillers, but also leads to their uneven distribution in the coating system, thereby affecting the final performance of the coating. Although the mechanical friction and impact in the ball milling process can achieve the dispersion of the components in the composite filler to a certain extent, the surface area provided by the grinding beads is relatively small, resulting in a low dispersion efficiency and poor dispersion effect of the composite nanofiller containing graphene in the ball milling process alone.
[0041] The present application provides a solution, specifically, a method for preparing a composite nanofiller, wherein a first powder is obtained by mixing graphene and graphene oxide and ball milling once, and then silicon dioxide is added to the first powder and ball milled twice to obtain a second powder; then titanium dioxide is added to the second powder and ball milled three times to obtain a third powder; then talcum powder, a silane coupling agent and the third powder are mixed and dispersed to obtain a composite nanofiller in the form of a slurry. The present application utilizes silicon dioxide and titanium dioxide with high hardness as auxiliary grinding media, so that graphene can be attached to silicon dioxide and / or titanium dioxide, significantly increasing the contact area between graphene and hard particles during ball milling, thereby effectively improving the dispersibility of graphene and graphene oxide. Furthermore, through the surface modification treatment of the silane coupling agent, the compatibility between the filler and the coating matrix in subsequent applications is promoted, ensuring the long-term stable dispersion of the filler in the coating system. In addition, the graphene oxide dispersed in the composite nanofiller can not only increase the corrosion resistance, toughness and impact resistance of the coating during the application process, but also play a certain dispersion and barrier role, which is more conducive to the uniformity and stability of the composite nanofiller during application, making the prepared composite nanofiller suitable for a variety of application scenarios.
[0042] Reference Figure 1 The first aspect of the embodiment of the present application provides a method for preparing a composite nanofiller, comprising the following steps:
[0043] Step S10, mixing graphene and graphene oxide and ball-milling them once to obtain a first powder;
[0044] In a feasible embodiment, graphene and graphene oxide are mixed in a mass ratio of 1:(0.05-0.3), and then 5-30 parts of the mixture of graphene and graphene oxide and 75-150 parts of anhydrous ethanol are added to a ball mill, and ball milling is performed once using high manganese steel balls or cast iron balls to obtain a first powder.
[0045] Anhydrous ethanol can dissolve, passivate and cover the surface of powder particles during ball milling, reduce the surface energy of particles, and thus promote particle refinement and dispersion. In addition, anhydrous ethanol can also generate forces such as hydrogen bonds and van der Waals forces, helping to form a closer physical bond between abrasives and powders, further promoting particle refinement.
[0046] Graphene has extremely high thermal conductivity, so when added to the paint as a filler, it can effectively conduct heat in the paint and improve the heat dissipation performance of the paint. In addition, the toughness, impact resistance and corrosion resistance of the paint can be significantly improved. But at the same time, there are very strong van der Waals forces and π-π effects between graphene sheets, which make it easy for graphene sheets to agglomerate together and difficult to disperse evenly in solvents or paints; and the specific surface area of graphene is very large, which makes its surface energy very high and easier to attract each other and agglomerate. Therefore, in the process of preparing composite nanofillers containing graphene, graphene is usually difficult to effectively disperse in the matrix and form agglomerates, resulting in a decrease in filler performance. Even if the composite nanofiller achieves uniform dispersion of graphene during the preparation process, when it is added to the paint, it may still cause the graphene to agglomerate again due to factors such as different coating systems, solvent selection, and coating stirring methods.
[0047] Due to its unique two-dimensional structure and high specific surface area, graphene oxide can also significantly improve the corrosion resistance, toughness and impact resistance of coatings when added to coatings as a filler. In addition, graphene oxide also has a certain dispersion barrier effect. During the preparation of coatings, nanofillers tend to agglomerate into blocks, affecting the uniformity and stability of the coating. However, graphene oxide can interact with other components in the coating to form a stable dispersion system because its surface contains abundant oxygen-containing functional groups (such as hydroxyl, carboxyl, etc.). At the same time, its lamellar structure can also effectively prevent the agglomeration of nanofillers and ensure the uniformity and stability of the filler in the coating.
[0048] Exemplarily, the mass ratio between graphene and graphene oxide can be 1:0.05, 1:0.06, 1:0.08, 1:0.1, 1:0.12, 1:0.14, 1:0.16, 1:0.18, 1:0.2, 1:0.22, 1:0.24, 1:0.26, 1:0.28, 1:0.3, etc.
[0049] For example, the added mixture of graphene and graphene oxide may be 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, etc. It should be understood that the "parts" mentioned in the embodiments of the present application represent parts by mass.
[0050] In a feasible implementation manner, the grinding time of a ball milling is 1.5 to 2 hours, the grinding temperature is 25 to 50° C., the main disk rotation speed is 200 to 400 rpm, and the grinding jar rotation speed is 300 to 450 rpm.
[0051] Exemplarily, the grinding time of a ball mill can be 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h, etc. The grinding temperature can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, etc. The main disk speed can be 200rpm, 240rpm, 260rpm, 280rpm, 300rpm, 320rpm, 340rpm, 360rpm, 380rpm, 400rpm, etc. The grinding jar speed can be 300rpm, 320rpm, 340rpm, 360rpm, 380rpm, 400rpm, 420rpm, 440rpm, 450rpm, etc.
[0052] Step S20, adding silicon dioxide to the first powder and performing a second ball milling to obtain a second powder;
[0053] In a feasible embodiment, 40 to 110 parts of silicon dioxide powder with a particle size of 200 to 500 nm are further added to the ball mill and ball milled for the second time to obtain a second powder.
[0054] Illustratively, the particle size of silica can be 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, 320 nm, 340 nm, 360 nm, 380 nm, 400 nm, 420 nm, 440 nm, 460 nm, 480 nm, 500 nm, etc.
[0055] Silicon dioxide as a filler can improve the stability of the coating and the hardness of the coating after film formation, and increase the specific heat capacity of the coating. The van der Waals force and other interaction forces between the large-sized nano-silicon dioxide particles selected in the embodiment of the present application are relatively weak, so it is not easy to gather together closely due to mutual attraction during the ball milling process; in addition, the large-sized nano-silicon dioxide can be attached to graphene, which increases the contact area between graphene and hard particles during the ball milling process, thereby promoting the dispersion of graphene and during the ball milling process, the size of the nano-silicon dioxide can be effectively reduced to ensure its performance.
[0056] For example, the added silicon dioxide may be 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, 110 parts, etc.
[0057] In a feasible implementation manner, the grinding time of the secondary ball milling is 2 to 3 hours, the main disc speed is 180 to 250 rpm, the grinding jar speed is 200 to 320 rpm, and the ball milling temperature can continue to be maintained at 25 to 50°C.
[0058] Exemplarily, the grinding time of the secondary ball milling can be 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h, 3h, etc. The main disc speed can be 180rpm, 190rpm, 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, etc. The grinding jar speed can be 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm, 300rpm, 310rpm, 320rpm, etc. Since silicon dioxide is further added to the secondary ball milling, the heat generation is relatively large, so the ball milling speed is appropriately reduced.
[0059] Step S30, adding titanium dioxide to the second powder and ball milling three times to obtain a third powder;
[0060] In a feasible embodiment, 30 to 80 parts of titanium dioxide powder with a particle size of 200 to 500 nm are further added to the ball mill and ball milled three times; after ball milling, the anhydrous ethanol is filtered out, and a vacuum treatment is performed for 30 to 45 minutes at a vacuum degree of 0.04 to 0.06 MPa and a drying temperature of 45 to 50° C. to remove air, moisture and other volatile impurities in the mixed powder; to prevent impurities from affecting the performance of the composite nanofiller, and to obtain a third powder.
[0061] Illustratively, the particle size of titanium dioxide can be 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, 320 nm, 340 nm, 360 nm, 380 nm, 400 nm, 420 nm, 440 nm, 460 nm, 480 nm, 500 nm, etc.
[0062] Titanium dioxide as a filler can improve the anti-aging and antibacterial effects of coatings. The interaction forces such as van der Waals force between the large-sized nano-titanium dioxide particles selected in the embodiment of the present application are relatively weak, so it is not easy to be closely agglomerated together due to mutual attraction during the ball milling process; in addition, the large-sized nano-titanium dioxide can be attached to graphene, which increases the contact area between graphene and hard particles during the ball milling process, thereby promoting the dispersion of graphene, and during the ball milling process, the size of the nano-titanium dioxide can be effectively reduced to ensure its performance.
[0063] For example, the amount of titanium dioxide added may be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, etc.
[0064] In one feasible implementation, the grinding time of the three ball millings is 2 to 3 hours, and the grinding temperature can be less than 65° C. Since grinding generates more heat after adding silicon dioxide and / or titanium dioxide, resulting in an increase in temperature, the grinding temperature is controlled to be less than 65° C., otherwise the added grinding medium (ethanol) may accelerate volatilization.
[0065] Exemplarily, the grinding time for the three ball millings can be 2 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h, 3 h, etc.
[0066] Exemplarily, the grinding jar speed of the third ball milling can be 200-320 rpm, for example, 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm, 300 rpm, 310 rpm, 320 rpm, etc. Since titanium dioxide is further added in the third ball milling, the heat generated is relatively large, so the ball milling speed is appropriately reduced compared with the first ball milling.
[0067] It should be understood that the hardness of silicon dioxide is slightly higher than that of titanium dioxide. Therefore, adding titanium dioxide first, or adding silicon dioxide and carbon dioxide together, may cause the silicon dioxide particle size to decrease more slowly during the ball milling process. Therefore, silicon dioxide is added to the ball mill first, and after the particle size is reduced to a certain extent, titanium dioxide is added to the ball mill, and the particle sizes of both are reduced to less than 200nm.
[0068] Step S40, mixing and dispersing talcum powder, silane coupling agent and the third powder to obtain a composite nano filler.
[0069] In a feasible embodiment, 100-130 parts of talc, 4-7 parts of silane coupling agent and the third powder are mixed and ultrasonically dispersed to prepare a composite nanofiller in the form of slurry.
[0070] Exemplarily, the added talcum powder can be 100 parts, 105 parts, 110 parts, 115 parts, 120 parts, 125 parts, 130 parts, etc. Talcum powder can improve the bonding force of the coating on the substrate surface during spraying and after curing. In addition, the silicon dioxide, titanium dioxide and talcum powder added in the embodiment of the present application can also play the role of coating skeleton, which is conducive to painting on the material surface.
[0071] For example, the amount of the added silane coupling agent may be 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, etc.
[0072] In one feasible implementation, the silane coupling agent includes: a first silane coupling agent and a second silane coupling agent, and step S40, mixing and dispersing talcum powder, the silane coupling agent and the third powder, and the step of preparing the composite nanofiller includes:
[0073] Step S41, providing a first silane coupling agent solution;
[0074] In a feasible embodiment, 450-500 parts of distilled water and 50-55 parts of anhydrous ethanol are mixed and heated to 35-50° C., the pH value is adjusted to 6-6.5, and then 1-2 parts of the first silane coupling agent are added and stirred for 0.5-2 hours to obtain a first silane coupling agent solution.
[0075] The first silane coupling agent usually needs to undergo a hydrolysis step before use to activate the reactive groups in its molecules so that it can more effectively chemically bond with the substrate surface or other materials to enhance interfacial compatibility and bonding strength. Therefore, it is necessary to prepare the first silane coupling agent solution first; and pH adjustment can accelerate the hydrolysis rate.
[0076] In one feasible embodiment, the first silane coupling agent includes at least one of KH-550, KH-560 and KH-570.
[0077] Step S42, mixing the third powder with the first silane coupling agent solution;
[0078] In a feasible embodiment, the third powder and the first silane coupling agent solution are mixed and stirred for 0.5 to 1 hour, and then the mixed solution is transferred into a metal dispersion tank in an ultrasonic tank and dispersed by a high-speed disperser for 20 to 30 minutes at a rotation speed of 1000 to 2500 rpm.
[0079] Exemplarily, the pH can be adjusted according to the properties of the resin contained in the coating when the composite nanofiller is used; for example, in the process of preparing the coating using the composite nanofiller, the water-based epoxy resin mixed with the composite nanofiller is alkaline, so after mixing the third powder and the first silane coupling agent solution, the pH value is adjusted to 7-7.5.
[0080] The first silane coupling agent has been partially or completely hydrolyzed before use to generate reactive silanol groups (Si-OH). These silanol groups can quickly undergo condensation reactions with hydroxyl groups (Si-OH, Ti-OH) on the surface of silicon dioxide and / or titanium dioxide to form stable chemical bonds and more fully combine with the surface of silicon dioxide or titanium dioxide, thereby covering the surface of silicon dioxide and titanium dioxide with a layer of organic groups to improve the dispersibility of nanoparticles.
[0081] Step S43, adding talcum powder and a second silane coupling agent, and performing ultrasonic dispersion to obtain a composite nanofiller.
[0082] In a feasible embodiment, 100-130 parts of talc powder with a mesh size of 12000 and 3-5 parts of a second silane coupling agent are further added, and ultrasonic dispersion is performed for 15-20 minutes to obtain a composite nanofiller in the form of a slurry.
[0083] For example, the amount of talc added may be 100 parts, 105 parts, 110 parts, 115 parts, 120 parts, 125 parts, 130 parts, etc.
[0084] For example, the amount of the second silane coupling agent added may be 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, etc.
[0085] The second silane coupling agent does not need to be pre-hydrolyzed and can directly react with talc, which simplifies the operation process. At the same time, the specific functional groups in the molecular structure of the second silane coupling agent can effectively react with active groups such as hydroxyl groups on the surface of talc to form stable chemical bonds, thereby providing effective surface modification for talc to reduce the agglomeration of talc and improve the uniformity and stability of the composite nanofiller.
[0086] In one feasible embodiment, the second silane coupling agent includes at least one of KH-550, KH-560, KH-570 and KH-792.
[0087] For example, the prepared composite nanofiller can be applied to various composite materials such as coatings, plastics, rubber, and ceramics.
[0088] In the present embodiment, silicon dioxide and titanium dioxide with high hardness are used as auxiliary grinding media, so that graphene can be attached to silicon dioxide and / or titanium dioxide, which significantly increases the contact area between graphene and hard particles during ball milling, thereby effectively improving the dispersibility of graphene and graphene oxide. Further, by surface modification treatment of silane coupling agent, the compatibility between filler and coating matrix in subsequent applications is promoted, ensuring the long-term stable dispersion of filler in coating system. In addition, graphene oxide dispersed in composite nanofiller can not only increase the corrosion resistance, toughness and impact resistance of coating during application, but also play a certain dispersion barrier role, which is more conducive to the uniformity and stability of composite nanofiller during application, so that the prepared composite nanofiller is suitable for a variety of application scenarios.
[0089] The second aspect of the embodiment of the present application provides a coating, comprising: the composite nanofiller as above. Since the composite nanofiller prepared as above is in the form of a uniform slurry, it can still maintain good dispersion uniformity when further added to the coating.
[0090] In a feasible embodiment, the coating further comprises: epoxy resin, wherein the mass ratio between the composite nano-filler and the epoxy resin is (3-5):(40-85).
[0091] Exemplarily, the epoxy resin includes: anionic, cationic or nonionic waterborne epoxy resin that matches the type of the silane coupling agent.
[0092] In one feasible embodiment, the method for preparing the coating comprises the following steps: providing a composite nanofiller, wherein the composite nanofiller is prepared by the above method; mixing the composite nanofiller with an epoxy resin, stirring evenly at 15 to 30° C. to prepare a coating, wherein the coating can be a water-based epoxy resin nanocoating.
[0093] Exemplarily, the stirring rate is 80 to 350 rpm, and the stirring time is 5 to 15 min.
[0094] In order to enable the details and operations of the above embodiments of the present application to be clearly understood by those skilled in the art, and to significantly demonstrate the improved performance of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.
[0095] Example 1
[0096] (1) adding 100 parts of anhydrous ethanol and 10 parts of a mixture of graphene and graphene oxide (mass ratio of 1:0.1) into a ball mill, adding high manganese steel balls, and setting the main disk speed to 300 rpm, the grinding jar speed to 400 rpm, grinding for 1.8 hours, and the grinding temperature to 40° C. to obtain a first powder;
[0097] (2) 80 parts of silicon dioxide powder with a particle size of 300 nm was further added to the first powder, the main disk speed was adjusted to 200 rpm, the grinding jar speed was adjusted to 250 rpm, and the grinding was performed for 2.5 hours to obtain a second powder at a grinding temperature of 40° C.;
[0098] (3) Add 60 parts of titanium dioxide powder with a particle size of 250 nm to the second powder and continue grinding for 2.5 hours at a grinding temperature of 50°C;
[0099] (4) taking out the mixed powder after ball milling, filtering to remove anhydrous ethanol, and drying at 0.05 MPa vacuum and 45° C. for 40 min to obtain a third powder;
[0100] (5) 475 parts of distilled water and 52 parts of anhydrous ethanol were mixed, stirred and heated to 45° C., the pH was adjusted to 6.2 with acetic acid, and 1.5 parts of KH-550 were added, and stirred for 1.5 hours to obtain a first silane coupling agent solution;
[0101] (6) Mix the third powder with the first silane coupling agent solution, stir for 0.8 h, adjust the pH value to 7.2 with sodium hydroxide, move into a metal dispersion tank in an ultrasonic tank, and perform high-speed dispersion treatment for 25 min at a speed of 2000 rpm;
[0102] (7) 120 parts of 12000 mesh talc powder were added, and 4 parts of KH-792 were added dropwise, and the dispersion treatment was continued for 18 minutes to obtain a composite nanofiller 1.
[0103] Example 2
[0104] (1) adding 120 parts of anhydrous ethanol and 15 parts of a mixture of graphene and graphene oxide (mass ratio of 1:0.2) into a ball mill, adding high manganese steel balls, and setting the main disk speed to 250 rpm, the grinding jar speed to 350 rpm, grinding for 2 h, and the grinding temperature to 35° C. to obtain a first powder;
[0105] (2) further adding 90 parts of silicon dioxide powder with a particle size of 250 nm to the first powder, adjusting the main disk speed to 220 rpm, the grinding jar speed to 300 rpm, grinding for 2.8 hours, and the grinding temperature to 40° C. to obtain a second powder;
[0106] (3) Add 70 parts of titanium dioxide powder with a particle size of 300 nm to the second powder and continue grinding for 3 hours at a grinding temperature of 60°C;
[0107] (4) taking out the mixed powder after ball milling, filtering to remove anhydrous ethanol, and drying at 0.06 MPa vacuum and 45° C. for 35 min to obtain a third powder;
[0108] (5) 480 parts of distilled water and 53 parts of anhydrous ethanol were mixed, heated to 40° C. with stirring, the pH was adjusted to 6.5 with acetic acid, and then 2 parts of KH-550 were added and stirred for 2 hours to obtain a first silane coupling agent solution;
[0109] (6) Mix the third powder with the first silane coupling agent solution, stir for 1 hour, adjust the pH value to 7.5 with sodium hydroxide, move into a metal dispersion tank in an ultrasonic tank, and perform high-speed dispersion treatment for 25 minutes at a speed of 2500 rpm;
[0110] (7) 110 parts of 12000 mesh talc powder were added, and 3.5 parts of KH-792 were added dropwise, and the dispersion treatment was continued for 20 minutes to obtain a composite nanofiller 2.
[0111] Example 3
[0112] (1) adding 90 parts of anhydrous ethanol and 8 parts of a mixture of graphene and graphene oxide (mass ratio of 1:0.15) into a ball mill, adding high manganese steel balls, and setting the main disk speed to 220 rpm, the grinding jar speed to 380 rpm, grinding for 1.7 hours, and the grinding temperature to 30° C. to obtain a first powder;
[0113] (2) 70 parts of silicon dioxide powder with a particle size of 220 nm was further added to the first powder, the main disk speed was adjusted to 200 rpm, the grinding jar speed was adjusted to 280 rpm, and the grinding was performed for 2.2 hours at a grinding temperature of 35° C. to obtain a second powder.
[0114] (3) Add 50 parts of titanium dioxide powder with a particle size of 280 nm to the second powder and continue grinding for 2.7 hours at a grinding temperature of 45°C;
[0115] (4) taking out the mixed powder after ball milling, filtering to remove anhydrous ethanol, and drying at 0.04 MPa vacuum and 38° C. for 50 min to obtain a third powder;
[0116] (5) 455 parts of distilled water and 50 parts of anhydrous ethanol were mixed, stirred and heated to 38° C., the pH was adjusted to 6.3 with acetic acid, and 1.2 parts of KH-550 were added, and stirred for 1 hour to obtain a first silane coupling agent solution;
[0117] (6) Mix the third powder with the first silane coupling agent solution, stir for 0.7 h, adjust the pH value to 7.3 with sodium hydroxide, move into a metal dispersion tank in an ultrasonic tank, and perform high-speed dispersion treatment for 22 min at a speed of 1800 rpm;
[0118] (7) 130 parts of 12000 mesh talc powder were added, and 4.5 parts of KH-792 were added dropwise, and the dispersion treatment was continued for 17 minutes to obtain composite nanofiller 3.
[0119] Example 4
[0120] (1) stirring 500 parts of acrylic acid-modified epoxy resin at a stirring temperature of 20° C. and a stirring rate of 120 rpm;
[0121] (2) slowly adding 35 parts of composite nanofiller 1 (prepared in Example 1) and stirring for 15 minutes to prepare a coating;
[0122] (3) The coating was sprayed on the workpiece surface at 90° C. and kept warm. After 20 minutes, the coating was moved into a 160° C. oven for curing for 15 minutes to obtain a waterborne epoxy resin coating 1 containing nanocomposite fillers.
[0123] Example 5
[0124] (1) stirring 650 parts of acrylic acid-modified epoxy resin at a temperature of 25° C. and a stirring rate of 180 rpm;
[0125] (2) slowly adding 50 parts of composite nanofiller 2 (prepared in Example 2) and stirring for 12 minutes to obtain a coating;
[0126] (3) The coating was sprayed on the workpiece surface at 95° C. and kept warm. After 25 minutes, the coating was moved into a 175° C. oven for curing for 12 minutes to obtain a waterborne epoxy resin coating 2 containing nanocomposite fillers.
[0127] Example 6
[0128] (1) stirring 800 parts of acrylic acid-modified epoxy resin at a stirring temperature of 30° C. and a stirring rate of 300 rpm;
[0129] (2) slowly adding 45 parts of composite nanofiller 3 (prepared in Example 3) and stirring for 8 minutes to obtain a coating;
[0130] (3) The coating was sprayed on the workpiece surface at 92° C. and kept warm. After 30 minutes, the coating was moved into a 165° C. oven for curing for 20 minutes to obtain a water-based epoxy resin coating 3 containing nanocomposite fillers.
[0131] Comparative Example 1
[0132] The experimental steps are the same as those of Example 1, except that the particle size of the added silicon dioxide is 50 nm, the particle size of the added titanium dioxide is 50 nm, and a composite nanofiller 4 is obtained.
[0133] Comparative Example 2
[0134] The experimental steps are the same as those of Example 1, except that silicon dioxide and titanium dioxide are not added to obtain the composite nanofiller 5.
[0135] Comparative Example 3
[0136] The experimental steps are the same as those of Example 4, except that a composite nanofiller 4 (prepared in Comparative Example 1) is added to obtain a water-based epoxy resin coating 4 containing a nanocomposite filler.
[0137] Comparative Example 4
[0138] The experimental steps are the same as those of Example 4, except that: a composite nano-filler 5 (prepared in Comparative Example 2) is added to obtain a water-based epoxy resin coating 5 containing a nano-composite filler.
[0139] Comparative Example 5
[0140] (1) stirring 500 parts of acrylic acid-modified epoxy resin at a stirring temperature of 20° C. and a stirring rate of 120 rpm;
[0141] (2) slowly adding 0.6 parts of graphene, 4.5 parts of silicon dioxide, 3.4 parts of titanium dioxide and 6.8 parts of talc in sequence and stirring for 15 minutes to prepare a coating;
[0142] (3) The coating was sprayed on the workpiece surface at 90° C. and kept warm. After 20 minutes, the coating was moved into a 160° C. oven for curing for 15 minutes to obtain a water-based epoxy resin coating 6 containing nanocomposite fillers.
[0143] The composite nano-fillers or coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were tested, and the results are shown in Table 1 below:
[0144] Table 1:
[0145]
[0146] According to the results of the above-mentioned Examples 1 to 3, the composite nanofiller prepared in the examples of the present application has good dispersion uniformity, and there is still no agglomeration or sedimentation after standing for 5 hours. Compared with Comparative Example 1, it can be seen that if the size of the silicon dioxide and titanium dioxide added to the filler is too small, the silicon dioxide and titanium dioxide will produce a nano-agglomeration effect, and a small amount of sedimentation will occur after standing for 5 hours. Further comparison with Comparative Example 2 shows that if silicon dioxide and titanium dioxide are not added, due to the large specific surface area of graphene, it is difficult to evenly disperse graphene into the filler, and more sedimentation will occur after standing for 5 hours.
[0147] According to the results of the above-mentioned Examples 4 to 6, the composite nanofiller prepared in the embodiments of the present application can be further applied to the coating and can also maintain good dispersibility. The obtained water-based epoxy resin coating containing nanocomposite fillers has no stratification after standing for 5 hours, and the coating resistivity is low; this is because the filler in the coating is evenly dispersed, so that the contact area between the filler particles and between the filler and the coating matrix is relatively large, and the transmission path of electrons in it is relatively smooth, so the resistivity of the coating will be relatively low, and the coating curing hardness will be improved. Compared with Example 3, it can be seen that if the size of the silicon dioxide and titanium dioxide added to the filler is too small, the components in the filler will produce a small amount of agglomeration, and the agglomeration will affect the uniformity of the coating during the film formation process of the coating, resulting in stratification of the coating and an increase in the resistivity of the coating, and the effect of improving the curing hardness of the coating is poor. Further comparison of Example 4 shows that if silicon dioxide and titanium dioxide are not added, the components in the filler will produce a large amount of agglomeration, resulting in a further increase in the resistivity of the coating, a poor effect on the improvement of the curing hardness of the coating, and stratification of the coating. Further comparison with Comparative Example 5 shows that if the components of the composite nanofiller are directly added to the coating matrix in sequence, the amount of filler added is limited, resulting in limited improvement in the curing hardness of the coating; and the added filler components are all solid, so they agglomerate in the coating matrix, resulting in an increase in the resistivity of the coating.
[0148] The above are only preferred embodiments of the present application, and do not limit the scope of the present application. For those skilled in the art, the present application may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of patent protection of the present application.
Claims
1. A method for preparing a composite nanofiller, characterized in that: The method comprises the following steps: Mixing graphene and graphene oxide and ball-milling them once to obtain a first powder; Adding silicon dioxide to the first powder and performing secondary ball milling to obtain a second powder; Adding titanium dioxide to the second powder and ball-milling the mixture three times to obtain a third powder; The talcum powder, the silane coupling agent and the third powder are mixed and dispersed to prepare a composite nano filler.
2. The method according to claim 1, characterized in that The particle size of the silicon dioxide is 200 to 500 nm; And / or, the particle size of the titanium dioxide is 200 to 500 nm.
3. The method according to claim 1, characterized in that The composite nanofiller comprises, by weight, 5 to 30 parts of a mixture of graphene and graphene oxide, 40 to 110 parts of silicon dioxide, 30 to 80 parts of titanium dioxide, 100 to 130 parts of talc and 4 to 7 parts of a silane coupling agent.
4. The method according to claim 1, characterized in that The mass ratio between graphene and graphene oxide is 1:(0.05-0.3).
5. The method according to claim 1, characterized in that The grinding time of the first ball milling is 1.5 to 2 hours, the grinding temperature is 25 to 50° C., the main disc speed is 200 to 400 rpm, and the grinding jar speed is 300 to 450 rpm; And / or, the grinding time of the secondary ball milling is 2 to 3 hours, the main disc speed is 180 to 250 rpm, and the grinding jar speed is 200 to 320 rpm; And / or, the grinding time of the three ball millings is 2 to 3 hours, and the grinding temperature is less than 65°C.
6. The method according to claim 1, characterized in that The silane coupling agent comprises: a first silane coupling agent and a second silane coupling agent, and the step of mixing and dispersing talcum powder, the silane coupling agent and the third powder to prepare the composite nano filler comprises: providing a first silane coupling agent solution; Mixing the third powder with the first silane coupling agent solution; Talc powder and a second silane coupling agent are added and ultrasonically dispersed to prepare a composite nanofiller.
7. The method according to claim 6, characterized in that The first silane coupling agent includes: at least one of KH-550, KH-560 and KH-570; And / or, the second silane coupling agent includes at least one of KH-550, KH-560, KH-570 and KH-792.
8. A composite nanofiller, characterized in that: The composite nanofiller is prepared by the method according to any one of claims 1 to 7.
9. A coating, characterized in that: The coating comprises: a composite nanofiller prepared by the method according to any one of claims 1 to 7.
10. The coating according to claim 9, characterized in that The coating further comprises: epoxy resin, wherein the mass ratio between the composite nano-filler and the epoxy resin is (3-5):(40-85).
